2022
DOI: 10.3390/agronomy12030552
|View full text |Cite
|
Sign up to set email alerts
|

Yields and Yield Gaps in Lowland Rice Systems and Options to Improve Smallholder Production

Abstract: Increasing productivity per unit area, hence closing the yield gap, is key to meeting cereal demand in sub-Saharan Africa. We assessed, with 114 farmers, the contribution of recommended agronomic practices (RAP) with or without NPK fertilization on yield gaps, and options to intensify productivity. Treatments included farmers’ practice (FP) as control, RAP with and without NPK, and farmer-selected best practices geared towards intensification (farmers’ intensification practice, FIP). RAP without fertilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
(126 reference statements)
0
7
1
Order By: Relevance
“…Even though lower-yielding farmers made larger yield gains, the overall yields recorded by farmers are still low, for the rice variety grown, when compared with yields observed under researcher-managed on-farm trials in the same study area (Awio et al, 2021). Grain yields recorded in this study are, however, higher than yields earlier reported under farmers' practice in the study area (Senthilkumar et al, 2020;Awio et al, 2022). The lack of yield gain by the top-yielding farmers might imply that at their current management level these farmers could not further raise their grain yields beyond the level observed during joint experimentation, probably because the observed current N input could be too low (which was up to a maximum of 68 kg N ha −1 after experimentation from 46 kg N ha −1 maximum rate during experimentation), in combination with lack of P and K application.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Even though lower-yielding farmers made larger yield gains, the overall yields recorded by farmers are still low, for the rice variety grown, when compared with yields observed under researcher-managed on-farm trials in the same study area (Awio et al, 2021). Grain yields recorded in this study are, however, higher than yields earlier reported under farmers' practice in the study area (Senthilkumar et al, 2020;Awio et al, 2022). The lack of yield gain by the top-yielding farmers might imply that at their current management level these farmers could not further raise their grain yields beyond the level observed during joint experimentation, probably because the observed current N input could be too low (which was up to a maximum of 68 kg N ha −1 after experimentation from 46 kg N ha −1 maximum rate during experimentation), in combination with lack of P and K application.…”
Section: Discussioncontrasting
confidence: 78%
“…The lack of yield gain by the top-yielding farmers might imply that at their current management level these farmers could not further raise their grain yields beyond the level observed during joint experimentation, probably because the observed current N input could be too low (which was up to a maximum of 68 kg N ha −1 after experimentation from 46 kg N ha −1 maximum rate during experimentation), in combination with lack of P and K application. It may therefore be necessary that farmers in this production system increase N rates, and P and K application be emphasised based on field inherent fertility to further raise grain yields as current farmers' fertilisation strategies do not put into consideration P and K application (Awio et al, 2022). This should be in addition to improved crop management practices, like proper timing of weeding and fertiliser application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pest-related effects of wider plant spacing include disease transmission, as well as management of weeds and insects (Castilla and Savary, 2003, Chauhan et al, 2011). Line sowing alongside timely weed management also has yield effects, aside from improved nutrient management (Awio et al, 2022). Such combined effects are typically difficult to measure as many factors are involved and outcomes are conditional on local circumstances.…”
Section: Discussionmentioning
confidence: 99%